3D animation modelling using After Effect in biogeochemical cycle study to develop cognitive activities. Issue 3 (March 2021) - Susanti, D; Rahmat, A; Amprasto, A
Abstract: The biogeochemical cycle is material that uses diagrams and is difficult to understand. Cognitive activity has a contribution in building understanding when studying a diagram. The purpose of this study was to obtain information about 3D animation modelling using after effect in biogeochemical cycle to develop cognitive activities. This research is a descriptive study. The model in this study is the biogeochemical cycle animation model using adobe after effect. Cognitive activity is measured before and during the study using a modelling example. All verbal data that appears is recorded and analysed according to think-aloud protocols (TAPs) which will then be translated and categorized into types of cognitive activity. The results of this study indicate that before using the modelling example the activity of activating the initial knowledge (K11) included in the high category. There was a development when study using modelling examples, namely elaboration (K41) most appeared with a high category. This study can be concluded that the 3D animation modelling using after effect can develop high-level cognitive activities, namely inference accurately (K31) and elaboration accurately (K41) in the biogeochemical cycle.